Metrics for Quality Assessment in Blockchain-based Systems: A Systematic Mapping Study - Saraiva, Raphael; Araújo, Allysson Allex; Soares, Pamella; Pontes, João Carlos; Souza, Jerffeson (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2025)
Context: Blockchain technology has been widely adopted across various industries, such as finance, healthcare, and logistics, due to its ability to ensure transaction integrity and transparency. Problem: The growing adoption of blockchain systems demands rigorous quality assessment to ensure compliance with requirements. While software metrics for centralized systems are well-studied, a clear research gap remains in understanding their systematic adoption for evaluating blockchain-based systems. Solution: This study identifies, analyzes, and categorizes software metrics used in blockchain-based systems assessment grounded on the quality characteristics of the ISO/IEC 25010 standard. IS Theory: The study uses the ISO/IEC 25010 as a theoretical foundation for classifying and analyzing quality metrics. Method: A Systematic Mapping Study was conducted, identifying 128 primary studies extracted from different academic databases. Results: The findings highlight performance and security as fundamental to quality in blockchain systems, focusing on throughput and latency metrics. Additionally, Hyperledger Caliper is a frequent tool for evaluating blockchain network performance. Smart contracts, on the other hand, emerge as a promising area, given the lack of studies exploring their security and efficiency. Contributions: This work enhances the understanding of quality assessment in blockchain systems by mapping software metrics to the ISO/IEC 25010, covering predominant metrics, quality characteristics, and evaluation methods.